Essentials of systems analysis and design - Valacich, Joseph S. (Pearson Prentice Hall, 2006)
In today's information and technology driven business world, student need to be aware of tree key factor. First, it is more crucial than ever to know how to organize and access information strategically. Second,success often depens on the ability to work as part of a team. Third, the internet will pay an important part in their work lives. Essentials of systems analysis and design, third edition, addresses these key factors.